PERBEDAAN KETEBALAN MEDIA FILTER BIO CERAMIC BALL TERHADAP PENURUNAN TOTAL COLIFORM PADA AIR MINUM DI PANTRY PT. Y (Jurnal Kesehatan Siliwangi, 2021)
Water is used by humans, so must meet the requirements. Drinking water available at the Pantry PT. Y uses processing from ultraviolet light, the results of the bacteriological examination do not meet the requirements for Coliform bacteria, which is 76 APM/100 ml, work-related disease data shows that employees have diarrheal disease in 2021. It is necessary to do additional processing with a filtration method using a ceramic filter. The aim of the study was to determine the difference in thickness of the bio ceramic ball filter on the total reduction of Coliform, with filter thicknesses of 10 cm, 15 cm, and 20 cm. The type of research is experimental, design is Pretest and Posttest without Control, the entire population of drinking water in the Pantry, a sample of some of the water taken from the population, grab sampling technique, the sample size is 36 samples. Data collection tools; laboratory equipment, pH meter, Thermometer, TDS meter.Tests carried out by One Way Anova. The results showed, 10 cm thickness decreased 58%, 15 cm decreased 73%, and 20 cm decreased 87%. So that there is a difference in the thickness of the bio ceramic ball filter on the decrease in total Coliform in drinking water. Further research by adding the thickness of the bio-ceramic ball filter to achieve quality standards for drinking water requirements according to the Regulation of the Minister of Health of the Republic of Indonesia No. 492 of 2010 or by combining drinking water treatment using a disinfection process.